1973
DOI: 10.1152/ajplegacy.1973.225.2.300
|View full text |Cite
|
Sign up to set email alerts
|

Effect of exhausting exercise on rat heart mitochondria

Abstract: The APS Journal Legacy Content is the corpus of 100 years of historical scientific research from the American Physiological Society research journals. This package goes back to the first issue of each of the APS journals including the American Journal of Physiology, first published in 1898. The full text scanned images of the printed pages are easily searchable. Downloads quickly in PDF format.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
11
0

Year Published

1982
1982
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(13 citation statements)
references
References 0 publications
2
11
0
Order By: Relevance
“…Previous studies of acute effects of exhaustive endurance exercise in various animal models have demonstrated varying degrees of changes and damage to the cardiac mitochondrial ultrastructure; ranging from no detected alterations [35, 45], mitochondrial hypertrophy with preserved structural integrity [46], to swelling and more extensive disruption [4750]. The discrepancies in findings have been suggested to be a result of a combination of different animal models, various exercise modes and diverse exercise intensities and durations.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies of acute effects of exhaustive endurance exercise in various animal models have demonstrated varying degrees of changes and damage to the cardiac mitochondrial ultrastructure; ranging from no detected alterations [35, 45], mitochondrial hypertrophy with preserved structural integrity [46], to swelling and more extensive disruption [4750]. The discrepancies in findings have been suggested to be a result of a combination of different animal models, various exercise modes and diverse exercise intensities and durations.…”
Section: Discussionmentioning
confidence: 99%
“…The subject has been controversial because only limited data are available and the various studies use different animal models and exercise regimens (cf. Terjung et al 1973). Meanwhile, considerable literature has accumulated indicating a detrimental role of strenuous exercise on mitochondrial function in skeletal muscle and liver (Davies et al 1982, Ji 1994 Recently, we proposed that ROS might also be involved in the pathology of heart mitochondrial dysfunction as a result of physical exercise .…”
Section: Discussionmentioning
confidence: 99%
“…Studies on myocardial mitochondria of endurance-trained animals are controver sial. Several studies have failed to show significant effects of endurance training [Bozner and Meessen, 1969;Gollnick et al, 1971;Guski et al, 1980;Kainulainen et al, 1979;Paniagua et al, 1977;Terzung et al, 1973]. In other cases changes in mitochon dria resulting from endurance training are very localized and have been attributed to focal areas of hypoxia [Arcos et al, 1967], It is possible that some ultrastructural degener ative changes in myocardial mitochondria are evident only in the early stages of train ing [Banister et al, 1971], which may be fol lowed by recovery and conditioning to stress with the result that significant changes in mitochondria of endurance-trained animals may be less easily detected [Arcos et al, 1967], Giant mitochondria have been reported in human myocardium [Harmjanz et al, 1971;Kraus and Cain, 1980] and in dogs subjected to brief periods of hypoxia [Ghadially, 1975] or experimental aortic stenosis [Wollenberger and Schulze, 1961], It is still not clear if giant mitochondria are formed by a simple enlargement of preexisting mito chondria, or by a process of fusion of several mitochondria, or by a combination of both processes [Ghadially, 1975], Our present studies indicate that a fusion of adjacent mitochondria occurs in the formation of the giant mitochondria.…”
Section: Discussionmentioning
confidence: 99%